The principle of least effort within the hierarchy of linguistic preferences: external evidence from English - Kul, Malgorzata (Unpublished PhD thesis, 2007)
The thesis is an investigation of the principle of least effort (Zipf 1949 [1972]). The principle is simple (all effort should be least) and universal (it governs the totality of human behavior). Since the principle is also functional, the thesis adopts a functional theory of language as its theoretical framework, i.e. Natural Linguistics. The explanatory system of Natural Linguistics posits that higher principles govern preferences, which, in turn, manifest themselves as concrete, specific processes in a given language. Therefore, the thesis’ aim is to investigate the principle of least effort on the basis of external evidence from English. The investigation falls into the three following strands: the investigation of the principle itself, the investigation of its application in articulatory effort and the investigation of its application in phonological processes. The structure of the thesis reflects the division of its broad aims. The first part of the thesis presents its theoretical background (Chapter One and Chapter Two), the second part of the thesis deals with application of least effort in articulatory effort (Chapter Three and Chapter Four), whereas the third part discusses the principle of least effort in phonological processes (Chapter Five and Chapter Six). Chapter One serves as an introduction, examining various aspects of the principle of least effort such as its history, literature, operation and motivation. It overviews various names which denote least effort, explains the origins of the principle and reviews the literature devoted to the principle of least effort in a chronological order. The chapter also discusses the nature and operation of the principle, providing numerous examples of the principle at work. It emphasizes the universal character of the principle from the linguistic field (low-level phonetic processes and language universals) and the non-linguistic ones (physics, biology, psychology and cognitive sciences), proving that the principle governs human behavior and choices. Chapter Two provides the theoretical background of the thesis in terms of its theoretical framework and discusses the terms used in the thesis’ title, i.e. hierarchy and preference. It justifies the selection of Natural Linguistics as the thesis’ theoretical framework by outlining its major assumptions and demonstrating its explanatory power. As far as the concepts of hierarchy and preference are concerned, the chapter provides their definitions and reviews their various understandings via decision theories and linguistic preference-based theories. Since the thesis investigates the principle of least effort in language and speech, Chapter Three considers the articulatory aspect of effort. It reviews the notion of easy and difficult sounds and discusses the concept of articulatory effort, overviewing its literature as well as various understandings in a chronological fashion. The chapter also presents the concept of articulatory gestures within the framework of Articulatory Phonology. The thesis’ aim is to investigate the principle of least effort on the basis of external evidence, therefore Chapters Four and Six provide evidence in terms of three experiments, text message studies (Chapter Four) and phonological processes in English (Chapter Six). Chapter Four contains evidence for the principle of least effort in articulation on the basis of experiments. It describes the experiments in terms of their predictions and methodology. In particular, it discusses the adopted measure of effort established by means of the effort parameters as well as their status. The statistical methods of the experiments are also clarified. The chapter reports on the results of the experiments, presenting them in a graphical way and discusses their relation to the tested predictions. Chapter Four establishes a hierarchy of speakers’ preferences with reference to articulatory effort (Figures 30, 31). The thesis investigates the principle of least effort in phonological processes, thus Chapter Five is devoted to the discussion of phonological processes in Natural Phonology. The chapter explains the general nature and motivation of processes as well as the development of processes in child language. It also discusses the organization of processes in terms of their typology as well as the order in which processes apply. The chapter characterizes the semantic properties of processes and overviews Luschützky’s (1997) contribution to NP with respect to processes in terms of their typology and incorporation of articulatory gestures in the concept of a process. Chapter Six investigates phonological processes. In particular, it identifies the issues of lenition/fortition definition and process typology by presenting the current approaches to process definitions and their typology. Since the chapter concludes that no coherent definition of lenition/fortition exists, it develops alternative lenition/fortition definitions. The chapter also revises the typology of phonological processes under effort management, which is an extended version of the principle of least effort. Chapter Seven concludes the thesis with a list of the concepts discussed in the thesis, enumerates the proposals made by the thesis in discussing the concepts and presents some questions for future research which have emerged in the course of investigation. The chapter also specifies the extent to which the investigation of the principle of least effort is a meaningful contribution to phonology.
Keywords: lenition